6 - Contribution à l'analyse essentielle de la tontine africaine: by Jean-Roger Essombe-Edimo - Jean-Roger Essombe-Edimo, (Africa Development, 1993)
Known by various names throughout Africa, rotating credit associations are first and foremost embodiments of social relations based on solidarity which function simultaneously as savings associations, credit association and a social good. Perceived within a unidimensional and reductionist perspective by economists these institutions are viewed as remnants which sustain financial dualism. Accordingly a significant feature of the financial stabilization and restructuring of the formal banking system in the context of structural adjustment projects currently underway is the attempt to unify the formal and informal sector in Africa through a reáůction of the weight of rotating Credit Association in saving mobilization in Africa. In Sub- sahar an Africa faced with the restructuring of the economy, increased unemployment, reduction of social services, decrease of salaries and overall household income, economic actors respond by accelerating socially based survival mechanisms such as rotating Credit Associations. Far from disappearing, therefore, there is a marked increase of financial transfer within these institutions at the expense of the banking systems.